2000
DOI: 10.1021/jp0024266
|View full text |Cite
|
Sign up to set email alerts
|

Micromanipulation of Langmuir-Monolayers with Optical Tweezers

Abstract: A technique for the manipulation of Langmuir-monolayers at the air/water interface is presented. Optical tweezers are combined with fluorescence and Brewster angle microscopy to produce a system capable of mechanical and thermal handling of monolayers on a micrometer scale. The viscoelastic, electrical, and thermodynamic properties of the monolayer can be determined by analysis of the perturbations of its structure. A method for force and heat calibration of the tweezers is given. Both kinds of micromanipulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 22 publications
2
50
0
Order By: Relevance
“…Given the previous measurements of the temperature rise in the 1064 nm continuous wave laser trap, and their corresponding range of the in situ powers and focal power densities2122232425, the temperature rise in our experiments is in the order of ≈1°C/100 mW in the focal volume. Such a temperature rise would be expected to have little, if any, biological consequence.…”
Section: Discussionsupporting
confidence: 56%
“…Given the previous measurements of the temperature rise in the 1064 nm continuous wave laser trap, and their corresponding range of the in situ powers and focal power densities2122232425, the temperature rise in our experiments is in the order of ≈1°C/100 mW in the focal volume. Such a temperature rise would be expected to have little, if any, biological consequence.…”
Section: Discussionsupporting
confidence: 56%
“…1͒. With a combination of optical tweezers and fluorescence microscopy 13 we simultaneously manipulate and visualize a Langmuir monolayer of methyl-octadecanoate. A single liquid condensed domain is forced to undergo combined translational and rotational motion.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the temperature rise was 10-20 T (degree)/W on focusing a sub-W trapping laser in water [41][42][43]. In the case of our higher laser power (270 mW), the temperature rise is estimated to be ≈ 6 K at most, thus not reaching to the transition temperature.…”
Section: Phase Transition Dynamicsmentioning
confidence: 73%